Knowledge, attitude and practice of smoking among pharmacy students: findings from a public university - Mohamed Ahmed, Abdul Karem; Elsayed, Tarek Mohamed Ali; Elkalmi, Ramadan Mohamed Mahmod; Jamshed, Shazia Qasim; Dyab, Eman Ali; Siddiqui, Mohammad Jamshed Ahmad; Nahas, Abdul Rahman Fata (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Smoking causes substantial preventable morbidity, mortality and financial burdens. It is the main risk factor for many diseases and a significant cause of death. Smoking prevalence is high internationally and in Malaysia, especially among males. Smoking cessation is essential to reduce tobacco-related morbidity and mortality. Aim: To evaluate knowledge, attitude towards and practice of smoking among pharmacy students in the International Islamic University Malaysia (IIUM). Materials and Methods: A cross-sectional study was conducted using a validated structured self-administered questionnaire among a sample of IIUM pharmacy students (n=251) during November 2012. Descriptive and inferential statistics were used to summarise data and to examine the relationship between variables. Results: A total of 251 IIUM pharmacy students have participated in the survey. The median age of the participants was 21-23 years; 23.9% of them were males and 76.1% were females. The percentage of current smokers and ex-smokers was 0.4%, 0.8%, respectively. About 43% of the respondents had a good knowledge (score >16), more than half of them had a positive attitude (score >17), and about 38.4% had a good practice (score >11). Conclusion: Smoking prevalence among pharmacy students in IIUM is very low. However, conducting training and educational programs to improve knowledge, attitudes and practice of pharmacy students is highly recommended to assist their contribution to smoking cessation interventions in the future.